Expression of mammalian sterile 20-like kinase 1 and 2 and Yes-associated protein 1 proteins in triple-negative breast cancer and the clinicopathological significance. Issue 34 (27th August 2021) - Feng, Yang; Ci, Hongfei; Wu, Qiong
Abstract: Background and aim: Mammalian sterile 20-like kinase 1 and 2 (MST1/2) and Yes-associated protein 1 (YAP1) are the core molecules of the Hippo signaling pathway, which have been found to be unbalanced in the occurrence of tumors and promote the development of the lesions. The present study aimed to investigate the expression of MST1/2 and YAP1 proteins in triple-negative breast cancer (TNBC) and their clinicopathological significance. Methods: Immunohistochemistry was used to detect the expression level of protein in tissues. According to the percentage of positive cells and staining intensity, the expression intensity of MST1/2 and YAP1 proteins in the tissue samples was scored, and the correlation between MST1/2 and the clinicopathological features of TNBC were discussed. Results: The expression of MST1/2 and YAP1 was associated with histological grade, metastasis, lymph node metastasis stage, and tumor node metastasis stage. The overexpression of YAP1 predicted a poor prognosis in terms of overall survival and disease-free survival time. The MST1/2 expression was associated with improved overall survival and disease free survival of the patients. Conclusion: MST1/2 and YAP1 may be used as prognostic indicators to evaluate the recurrence of TNBC and might become one of the new targets for breast cancer treatment.